Fine structure of critical opalescence spectra - Sushko, M.Ya. (Физика низких температур, 2007)
The effect of the 1.5-scattering mechanism on the time and temperature behavior of the electric field
autocorrelation function for the light wave scattered from fluids has been studied for the case where the order-
parameter fluctuations obey the diffusion-like kinetics with spatially-dependent kinetic coefficient. The
leading contributions to the relevant static correlation functions of the order-parameter fluctuations were
obtained by using the Ginzburg–Landau model with a cubic term, and then evaluated with the use of the
Gaussian uncoupling for many-point correlation functions and the Ornstein–Zernicke form for the pair correlation
function. It is shown that the presence of the 1.5-scattering effects in the overall scattering pattern
may be detected in the form of a small but noticeable deviation from exponential decay of the total electric
field autocorrelation function registered experimentally near the critical point. Obtained with the standard
methods of analysis, the effective halfwidth of the corresponding spectrum can reveal a stronger temperature
dependence and a multiplicative renormalization as compared to the halfwidth of the spectrum of the
pair correlator.